Corrigendum to “Mycoplasma bovis outbreaks in United States bison (Bison bison) herds: A case-control survey” [Prev. Vet. Med. 243 (2025) 106597] - Kelsey A. Martin; A. Springer Browne; Danielle E. Buttke (Preventive Veterinary Medicine, 2026)

Genomic Insights Into the Evolutionary History of Berardius Beaked Whales: Speciation Driven by Resource Specialization, Gigantism and Thermal Barriers? - Morgan L. McCarthy; Michael V. Westbury; Mark S. Springer; John Gatesy; Morten Tange Olsen; Phillip A. Morin (Molecular Ecology, 2026)
Understanding the diversity of our oceans is fundamental now more than ever as climate change and human activities put increasing pressure on marine species and ecosystems. Beaked whales (family Ziphiidae) are among the most poorly understood marine mammals, in part due to their affinity to offshore underwater canyons and prolonged diving ability. The ziphiid genus Berardius is comprised of three extant species; however, a lack of genomic data results in uncertainties of their evolutionary origin, phylogenetic relationships and the past environmental drivers of speciation and demographic fluctuations. Here, we analyse whole nuclear and mitochondrial genomes to better understand the evolutionary and demographic history of Berardius spp. Genome‐wide comparisons support an initial divergence of B. minimus from the B. bairdii – B. arnuxii common ancestor ~4 million years ago (mya), and a divergence between B. bairdii and B. arnuxii ~1.5 mya. Despite these deep divergence times, gene flow was detected between species pairs for at least 75% of their post‐divergence branch lengths. Strong levels of introgression (~8%) were detected between the non‐sister but geographically overlapping B. bairdii and B. minimus species, despite their significant differences in body size. Our results show that the Berardius speciation process goes beyond simple bifurcating divergences. We hypothesize that resource specialization and an increased body size in the B. bairdii – B. arnuxii ancestor may have been an incipient driver of speciation and further that climate cycles during the late Pleistocene, coupled with ranging movements to the tropics, could have permitted repeated opportunities for gene flow between species.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

High-definition tDCS of the motor cortex affects prefrontal and primary motor activity differently in young and older adults - Yasra Arif; Peihan J. Huang; Seth D. Springer; Hannah J. Okelberry; Jason A. John; Nathan M. Petro; Grant M. Garrison; Kennedy A. Kress; Kellen M. McDonald; Giorgia Picci; Tony W. Wilson (GeroScience, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Mycoplasma bovis outbreaks in United States bison (Bison bison) herds: A case-control survey - Kelsey A. Martin; A. Springer Browne; Danielle E. Buttke (Preventive Veterinary Medicine, 2025)

Oscillatory Dynamics Serving Verbal Working Memory Differ in People with HIV and Are Linked To Disease Duration - Kellen M. McDonald; Seth D. Springer; Mikki Schantell; Ryan Glesinger; Lucy K. Horne; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Madelyn P. Willett; Hallie J. Johnson; Rachel K. Spooner; Tony W. Wilson (Journal of Neuroimmune Pharmacology, 2025)
Background Medical advances have greatly improved the quality of life and extended the longevity of people with HIV (PWH). However, many PWH still develop neurocognitive deficits even in the presence of effective viral suppression, with impairments in verbal working memory (VWM) being among the most common. While previous neuroimaging studies have demonstrated altered neural responses during VWM, the underlying temporal dynamics and their relation to clinical indices of HIV remain poorly understood. Hypothesis PWH will have altered neural oscillatory dynamics in brain regions supporting VWM compared to controls, above and beyond the effect of age, and these oscillatory differences will scale with clinical indices of HIV. Methods 166 participants (77 virally-suppressed PWH, 89 demographically-matched controls) completed a VWM task during magnetoencephalography, which was separated into encoding and maintenance phases. Whole-brain, mixed-model ANCOVAs were performed to assess the effects of HIV status on neural dynamics controlling for age. Results PWH performed significantly worse on the task compared to controls. During encoding, there was a significant interaction of group-by-time window, such that PWH had significantly weaker alpha/beta oscillations in the left inferior frontal, superior temporal, and anterior cingulate relative to controls. Further, weaker activity in the anterior cingulate scaled with increased disease duration. PWH also displayed weaker alpha/beta oscillations during maintenance in frontal, temporal, parietal, anterior cingulate, and cerebellar cortices. Conclusions PWH exhibited weaker task-related oscillatory activity during VWM, which was associated with disease duration in the anterior cingulate. Overall, these findings suggest that HIV modulates the neural dynamics underlying VWM, with progressive effects in some areas.

Spatiotemporal Dynamics of Non‐Ecological Speciation in Rubyspot Damselflies ( Hetaerina spp.) - C. Patterson; A. Brennan; H. Cowling; A. González‐Rodríguez; G. F. Grether; L. Mendoza Cuenca; M. Springer; Y. M. Vega‐Sánchez; J. Drury (Molecular Ecology, 2025)
Non‐ecological speciation is a common mode of speciation, which occurs when allopatric lineages diverge in the absence of pronounced ecological differences. Yet, relative to other speciation mechanisms, non‐ecological speciation remains understudied. Numerous damselfly clades are characterised as non‐adaptive radiations (the result of several rounds of non‐ecological speciation without subsequent divergence), but there are few damselfly lineages for which we have a detailed understanding of the spatiotemporal dynamics of divergence. Recent phylogeographic analyses demonstrate that American rubyspot damselflies ( Hetaerina americana sensu lato) actually comprise at least two cryptic lineages that coexist sympatrically across most of Mexico. To broaden our understanding of the dynamics of diversification to other rubyspot lineages, we investigated the phylogeographic history of smoky rubyspot damselflies ( Hetaerina titia ) using genomic data collected across Central and North America. Unexpectedly, we found evidence of reproductive isolation between the highly genetically differentiated Pacific and Atlantic lineages of H. titia in a narrow secondary contact zone on the Isthmus of Tehuantepec, Mexico. We then fit models of historical demography to both H. americana sensu lato and H. titia to place these comparisons in a temporal context. Our findings indicate that Pacific and Atlantic lineages of H. titia split more recently than the broadly sympatric lineages within H. americana sensu lato, supporting key assumptions of the non‐ecological speciation model and demonstrating that these two pairs of sister lineages are at different stages of the speciation cycle.

Impacts of repeated fatiguing exercise on mitochondria in Thoroughbreds - B.D. Williams; L.T. Wesolowski; A.N. DiSilvestro; M. Barshick; K. Mogge; E. Jolley; K. Kaniyamattam; A. Logan; S. Johnson; S.H. White-Springer (Journal of Equine Veterinary Science, 2025)

Assessing the impact of ostarine on body composition in adult horses: A longitudinal study - A. Morocho; A.C. Herbst; S.H. White-Springer; K. Malinowski; K.H. McKeever (Journal of Equine Veterinary Science, 2025)

Multi-Step Forecasting of Meteorological Time Series Using CNN-LSTM with Decomposition Methods - Eluã Ramos Coutinho; Jonni G. F. Madeira; Dérick G. F. Borges; Marcus V. Springer; Elizabeth M. de Oliveira; Alvaro L. G. A. Coutinho (Water Resources Management, 2025)

IFN-γ/IL-2 Double-Color FluoroSpot Assay for Monitoring Human Primary T Cell Activation: Validation, Inter-Laboratory Comparison, and Recommendations for Clinical Studies - Alexandra Mauthe; Edward Cedrone; Raquel Villar-Hernández; Elisa Rusch; Marco Springer; Martin Schuster; Rosemarie Preyer; Marina A. Dobrovolskaia; Matthias Gutekunst (The AAPS Journal, 2025)
The enzyme-linked immunosorbent spot (EliSpot) assay and its fluorescence-based version, FluoroSpot, are sensitive immunoassays commonly used to quantify antigen-specific T and B lymphocytes and other immune cells in peripheral blood or homogenized tissues. Due to their high sensitivity, these assays are popular in clinical trials to evaluate the efficacy of immunotherapy and vaccines, which involve a high level of scrutiny to ensure valid study results. Besides industry consensus white papers and other research publications, there is no formal guidance for the industry on how to validate EliSpot and FluoroSpot assays to ensure their accurate performance for immune monitoring in clinical trials. Herein, we describe a comprehensive in vitro study using healthy human donor peripheral blood mononuclear cells (PBMCs) and model antigens to validate a double-color FluoroSpot assay for monitoring antigen-specific lymphocytes by detecting and quantifying IFN-γ and IL-2-producing lymphocytes. Validation parameters, acceptance criteria set-up, and assay limits—limit of detection (LOD), minimum positive control response, lower and upper limits of quantification (LLOQ and ULOQ)—were determined, and assay performance was demonstrated by assessing precision, specificity, linearity, and robustness. In addition, an inter-laboratory comparison demonstrated concordance between assay results from two laboratories. In summary, this study outlines a robust approach to EliSpot and FluoroSpot validation and demonstrates that the IFN-γ/IL-2 FluoroSpot assay is suitable for the reliable detection of antigen-specific immune responses from PBMC samples across laboratories and meets the current regulatory requirements for bioanalytical method validation. Graphical Abstract

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Local and systemic responses to repeated gluteal muscle microbiopsies in mature sedentary horses - Jessica L. Artman; Lauren T. Wesolowski; Pier L. Semanchik; JadaLea K. Isles; Sharon A. Norton; Sarah H. White-Springer (Journal of Equine Veterinary Science, 2024)

Non-native plant invasion after fire in western USA varies by functional type and with climate - Janet S. Prevéy; Catherine S. Jarnevich; Ian S. Pearse; Seth M. Munson; Jens T. Stevens; Kevin J. Barrett; Jonathan D. Coop; Michelle A. Day; David Firmage; Paula J. Fornwalt; Katharine M. Haynes; James D. Johnston; et al. (Biological Invasions, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Assessment of the Palatability and Acceptability of Hempseed Meal Pellets in Horses Compared to Mainstream Feedstuffs - Ryon W. Springer; A. Cheyenne Mason; Teighlor D. Cross; Kimberly A. Guay; Randel H. Raub; Kimberly B. Wellmann; Trinette N. Jones (Journal of Equine Veterinary Science, 2023)

Refuge‐yeah or refuge‐nah? Predicting locations of forest resistance and recruitment in a fiery world - Kyle C. Rodman; Kimberley T. Davis; Sean A. Parks; Teresa B. Chapman; Jonathan D. Coop; Jose M. Iniguez; John P. Roccaforte; Andrew J. Sánchez Meador; Judith D. Springer; Camille S. Stevens‐Rumann; Michael T. Stoddard; Amy E. M. Waltz; et al. (Global Change Biology, 2023)
Climate warming, land use change, and altered fire regimes are driving ecological transformations that can have critical effects on Earth's biota. Fire refugia—locations that are burned less frequently or severely than their surroundings—may act as sites of relative stability during this period of rapid change by being resistant to fire and supporting post‐fire recovery in adjacent areas. Because of their value to forest ecosystem persistence, there is an urgent need to anticipate where refugia are most likely to be found and where they align with environmental conditions that support post‐fire tree recruitment. Using biophysical predictors and patterns of burn severity from 1180 recent fire events, we mapped the locations of potential fire refugia across upland conifer forests in the southwestern United States (US) (99,428 km 2 of forest area), a region that is highly vulnerable to fire‐driven transformation. We found that low pre‐fire forest cover, flat slopes or topographic concavities, moderate weather conditions, spring‐season burning, and areas affected by low‐ to moderate‐severity fire within the previous 15 years were most commonly associated with refugia. Based on current (i.e., 2021) conditions, we predicted that 67.6% and 18.1% of conifer forests in our study area would contain refugia under moderate and extreme fire weather, respectively. However, potential refugia were 36.4% (moderate weather) and 31.2% (extreme weather) more common across forests that experienced recent fires, supporting the increased use of prescribed and resource objective fires during moderate weather conditions to promote fire‐resistant landscapes. When overlaid with models of tree recruitment, 23.2% (moderate weather) and 6.4% (extreme weather) of forests were classified as refugia with a high potential to support post‐fire recruitment in the surrounding landscape. These locations may be disproportionately valuable for ecosystem sustainability, providing habitat for fire‐sensitive species and maintaining forest persistence in an increasingly fire‐prone world.

Confounding effects of snow cover on remotely sensed vegetation indices of evergreen and deciduous trees: An experimental study - Ran Wang; Kyle R. Springer; John A. Gamon (Global Change Biology, 2023)
Located at northern latitudes and subject to large seasonal temperature fluctuations, boreal forests are sensitive to the changing climate, with evidence for both increasing and decreasing productivity, depending upon conditions. Optical remote sensing of vegetation indices based on spectral reflectance offers a means of monitoring vegetation photosynthetic activity and provides a powerful tool for observing how boreal forests respond to changing environmental conditions. Reflectance‐based remotely sensed optical signals at northern latitude or high‐altitude regions are readily confounded by snow coverage, hampering applications of satellite‐based vegetation indices in tracking vegetation productivity at large scales. Unraveling the effects of snow can be challenging from satellite data, particularly when validation data are lacking. In this study, we established an experimental system in Alberta, Canada including six boreal tree species, both evergreen and deciduous, to evaluate the confounding effects of snow on three vegetation indices: the normalized difference vegetation index (NDVI), the photochemical reflectance index (PRI), and the chlorophyll/carotenoid index (CCI), all used in tracking vegetation productivity for boreal forests. Our results revealed substantial impacts of snow on canopy reflectance and vegetation indices, expressed as increased albedo, decreased NDVI values and increased PRI and CCI values. These effects varied among species and functional groups (evergreen and deciduous) and different vegetation indices were affected differently, indicating contradictory, confounding effects of snow on these indices. In addition to snow effects, we evaluated the contribution of deciduous trees to vegetation indices in mixed stands of evergreen and deciduous species, which contribute to the observed relationship between greenness‐based indices and ecosystem productivity of many evergreen‐dominated forests that contain a deciduous component. Our results demonstrate confounding and interacting effects of snow and vegetation type on vegetation indices and illustrate the importance of explicitly considering snow effects in any global‐scale photosynthesis monitoring efforts using remotely sensed vegetation indices.

Human perceptions of competing interests in springs ecosystem management on public land in southwestern United States - Andrew J. Lewis; Stefanie Kunze; Julie M. Mueller; Ryan A. Fitch; Abraham E. Springer (Groundwater for Sustainable Development, 2023)

183 Effects of prolonged hay net feeding on equine behavior - M.R. Locke; T.D. Cross; A. Hoglan; R. Springer; K.A. Guay; K. Wellmann; R. Martínez; T.N. Jones (Journal of Equine Veterinary Science, 2023)

59 Inter-rater reliability of equine nutrition screening tools in a clinical setting - A. Self; M.T. Hines; C. Springer; L.G. Strickland; K. McCormick; J.L.-Z. Ivey (Journal of Equine Veterinary Science, 2023)

Anatomical, Ontogenetic, and Genomic Homologies Guide Reconstructions of the Teeth-to-Baleen Transition in Mysticete Whales - John Gatesy; Eric G. Ekdale; Thomas A. Deméré; Agnese Lanzetti; Jason Randall; Annalisa Berta; Joseph J. El Adli; Mark S. Springer; Michael R. McGowen (Journal of Mammalian Evolution, 2022)

A Novel Computational Approach Coupled with Machine Learning to Predict the Extent of Agglomeration in Particulate Processes - Kushal Sinha; Eric Murphy; Prashant Kumar; Kirsten A. Springer; Raimundo Ho; Nandkishor K. Nere (AAPS PharmSciTech, 2021)

Stakeholder Perceptions of White Oak Supply in Kentucky: A SWOT-AHP Analysis - William R. Thomas; Thomas O. Ochuodho; Chad F. Niman; Matthew T. Springer; Domena A. Agyeman; Laura R. Lhotka (Small-scale Forestry, 2021)

The clinical and educational outcomes of an inter-professional student-led medication review team, a pilot study - Michael O. Reumerman; Milan C. Richir; Philippe M. Domela Nieuwenhuis; Rowan Sultan; Hester E. M. Daelmans; Hans Springer; Majon Muller; Michiel A. van Agtmael; Jelle Tichelaar (European Journal of Clinical Pharmacology, 2021)
Aims The involvement of an inter-professional healthcare student team in the review of medications used by geriatric patients could not only provide patients with optimized therapy but also provide students with a valuable inter-professional learning experience. We describe and evaluate the clinical and learning outcomes of an inter-professional student-run mediation review program (ISP). Subject and method A variable team consisting of students in medicine, pharmacy, master advanced nursing practice, and master physician assistant reviewed the medication lists of patients attending a specialized geriatric outpatient clinic. Results During 32 outpatient visits, 188 medications were reviewed. The students identified 14 medication-related problems, of which 4 were not recognized by healthcare professionals. The ISP team advised 95 medication changes, of which 68 (71.6%) were directly implemented. Students evaluated this pilot program positively and considered it educational (median score 4 out of 5) and thought it would contribute to their future inter-professional relationships. Conclusion An inter-professional team of healthcare students is an innovative healthcare improvement for (academic) hospitals to increase medication safety. Most formulated advices were directly incorporated in daily practice and could prevent future medication-related harm. The ISP also offers students a first opportunity to work in an inter-professional manner and get insight into the perspectives and qualities of their future colleagues.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Effect of removal of bacteria on the biomass and extracellular carbohydrate productivity of Botryococcus braunii - Joao D. Gouveia; Antoine Moers; Yvonne Griekspoor; Lambertus A. M. van den Broek; Jan Springer; Lolke Sijtsma; Detmer Sipkema; Rene H. Wijffels; Maria J. Barbosa (Journal of Applied Phycology, 2019)

Modeling intrinsic vulnerability of complex karst aquifers: modifying the COP method to account for sinkhole density and fault location - Natalie A. Jones; Jered Hansen; Abraham E. Springer; Cynthia Valle; Benjamin W. Tobin (Hydrogeology Journal, 2019)

Correction to: Lung cancer screening: an emerging cancer control issue presents opportunities for an awareness campaign in rural Michigan - Steven M. Springer; Angela McFall; Polly Hager; Antoinette Percy-Laurry; Cynthia A. Vinson (Cancer Causes & Control, 2019)

Evidence of daily hydrological loading in GPS time series over Europe - Anne Springer; Makan A. Karegar; Jürgen Kusche; Jessica Keune; Wolfgang Kurtz; Stefan Kollet (Journal of Geodesy, 2019)

Lung cancer screening: an emerging cancer control issue presents opportunities for an awareness campaign in rural Michigan - Steven M. Springer; Angela McFall; Polly Hager; Antoinette Percy-Laury; Cynthia A. Vinson (Cancer Causes & Control, 2018)

Erratum to: Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

Low ambient oxygen prevents atherosclerosis - Ju-Gyeong Kang; Ho Joong Sung; Marcelo J. Amar; Milton Pryor; Alan T. Remaley; Michele D. Allen; Audrey C. Noguchi; Danielle A. Springer; Jaeyul Kwon; Jichun Chen; Ji-hoon Park; Ping-yuan Wang; et al. (Journal of Molecular Medicine, 2016)

A complete VLBI delay model for deforming radio telescopes: the Effelsberg case - T. Artz; A. Springer; A. Nothnagel (Journal of Geodesy, 2014)

Parallel evolution of a self-signal: humans and new world monkeys independently lost the cell surface sugar Neu5Gc - Stevan A. Springer; Sandra L. Diaz; Pascal Gagneux (Immunogenetics, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Metabolic syndrome in mice induced by expressing a transcriptional activator in adipose tissue - Liwen Zhang; Yuchen Zhou; Amber Ying Zhu; Xiang-qing Li; Steven S. Mundt; Ling Gao; JeanMarie Lisnock; Melba Hernandez; Magdalena Alonso-Galicia; Martin S. Springer; Edward A. O’Neill; Bruce L. Daugherty; et al. (Transgenic Research, 2012)

A Phylogeny and Timescale for the Evolution of Pseudocheiridae (Marsupialia: Diprotodontia) in Australia and New Guinea - Robert W. Meredith; Miguel A. Mendoza; Karen K. Roberts; Michael Westerman; Mark S. Springer (Journal of Mammalian Evolution, 2010)

Trend data do support the sequential nature of pinniped and sea otter declines in the North Pacific Ocean, but does it really matter? - J. A. Estes; D. F. Doak; A. M. Springer; T. M. Williams; G. B. Van Vliet (Marine Mammal Science, 2009)

Nocturnal activity by mammal‐eating killer whales at a predation hot spot in the Bering Sea - K. Newman; A. M. Springer (Marine Mammal Science, 2008)

Tracing carbon flow in an arctic marine food web using fatty acid-stable isotope analysis - S. M. Budge; M. J. Wooller; A. M. Springer; S. J. Iverson; C. P. McRoy; G. J. Divoky (Oecologia, 2008)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Mammal‐eating killer whales, industrial whaling, and the sequential megafaunal collapse in the North Pacific Ocean: A reply to critics of Springer et al . 2003 - A. M. Springer; J. A. Estes; G. B. Van Vliet; T. M. Williams; D. F. Doak; E. M. Danner; B. Pfister (Marine Mammal Science, 2008)

A Phylogeny and Timescale for Marsupial Evolution Based on Sequences for Five Nuclear Genes - Robert W. Meredith; Michael Westerman; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2008)

Fatty acid signatures of stomach oil and adipose tissue of northern fulmars (Fulmarus glacialis) in Alaska: implications for diet analysis of Procellariiform birds - Shiway W. Wang; Sara J. Iverson; Alan M. Springer; Scott A. Hatch (Journal of Comparative Physiology B, 2007)

Environment-specific heterozygote deficiency and developmental instability in hybrid Mytilus - Stevan A. Springer; Daniel D. Heath (Marine Biology Research, 2007)

Soil calcium and plant disease in serpentine ecosystems: a test of the pathogen refuge hypothesis - Yuri P. Springer; Bree A. Hardcastle; Gregory S. Gilbert (Oecologia, 2007)

Comprehensive trend analysis of nutrients and related variables in a large eutrophic estuary: A decadal study of anthropogenic and climatic influences - JoAnn M. Burkholder; David A. Dickey; Carol A. Kinder; Robert E. Reed; Michael A. Mallin; Matthew R. McIver; Lawrence B. Cahoon; Greg Melia; Cavell Brownie; Joy Smith; Nora Deamer; Jeffrey Springer; et al. (Limnology and Oceanography, 2006)
We used a decadal data set, with weekly to biweekly sampling in April—October and monthly sampling in November—March, to characterize climatic (hurricane‐level storms, a sustained 3‐yr drought) and anthropogenic influences on N and P concentrations and loadings to a large eutrophic, poorly flushed estuary, the Neuse Estuary of the Albemarle—Pamlico Estuarine System. Mass volume transport data were obtained with cross‐estuary transect flow measurements taken near the entrance to the estuary. Although trends were minimally influenced by hurricanes, analyses were significantly affected by the sustained drought near the end of the study. As examples, decreasing trends in total N (TN), total P (TP), and bottom‐water dissolved oxygen concentrations, and in TN loadings were significant considering all data, but these trends were not significant when the sustained drought was excluded from analysis. In addition, the trend in TN loading was especially sensitive to the initial sampling period. NH 4 + concentrations dramatically increased (overall by ~500%) as a persistent trend regardless of attempts to control for climatic events. An increasing trend in NH 4 + also was documented in an adjacent, rapidly flushed Coastal Plain estuary, the Cape Fear. The NH 4 + data suggest a regional‐scale effect of high inputs from inadequately controlled, increasing nonpoint sources. The fragility of TN loading trends, the striking increase in NH 4 + concentrations, and the lack of management emphasis on controlling nonpoint sources such as “new” industrialized swine production collectively do not support recent reports of achievement of a 30% reduction in TN loading to the Neuse. Nonpoint sources remain a critical target for reduction to alleviate the negative effects of cultural eutrophication in this system, as in many estuaries throughout the world.

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A New Interpretation of Avian and Mammalian Reproduction Toxicity Test Data in Ecological Risk Assessment - Richard S. Bennett; I.C. Dewhurst; A. Fairbrother; A.D.M. Hart; M.J. Hooper; A. Leopold; P. Mineau; S.R. Mortensen; R.F. Shore; T.A. Springer (Ecotoxicology, 2005)

Hepatotoxic effects of polidocanol in a model of autologously perfused porcine livers - Christian Grosse-Siestrup; Volker Unger; Jeanette Pfeffer; Q. Thai Dinh; Stefan Nagel; Jochen Springer; Christian Witt; Anke Wussow; David A. Groneberg (Archives of Toxicology, 2004)

Molecular Evidence for the Last Survivor of an Ancient Kangaroo Lineage - Michael Westerman; Angela Burk; Heather M. Amrine-Madsen; Gavin J. Prideaux; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2002)

The international GLONASS experiment: products, progress and prospects - R. Weber; T. A. Springer (Journal of Geodesy, 2001)

Improving the orbit estimates of GPS satellites - T. A. Springer; G. Beutler; M. Rothacher (Journal of Geodesy, 1999)

A New Solar Radiation Pressure Model for GPS Satellites - T. A. Springer; G. Beutler; M. Rothacher (GPS Solutions, 1999)

Cervical lymphadenitis due to an unusual mycobacterium - E. Tortoli; P. Kirschner; B. Springer; A. Bartoloni; C. Burrini; A. Mantella; M. Scagnelli; C. Scarparo; M. T. Simonetti; E. C. Böttger (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Impact of salt adaptation on esterified fatty acids and cytochrome oxidase in plasma and thylakoid membranes from the cyanobacterium Anacystis nidulans - V. Molitor; M. Trnka; W. Erber; I. Steffan; M. -E. Rivire; B. Arrio; H. Springer-Lederer; G. A. Peschek (Archives of Microbiology, 1990)